Bombyx mori silk-based materials with implication in skin repair: Sericin versus regenerated silk fibroin. (July 2019) - Su, Dihan; Ding, Shenglong; Shi, Weiliang; Huang, Xuefeng; Jiang, Libo
Recently, regenerated silk fibroin is one of the most investigated silk-based materials for tissue engineering. However, it needs complex preparation process and will irresistibly denature to solid state with time, which is the biggest challenge to produce in large scale and widely use it as commercial material. In this work, industrially produced sericin, silk fibroin amino acid, and silk fibroin powder were investigated on its physico–chemical and biological properties compared with laboratory prepared regenerated silk fibroin, in order to excavate the potential application in biomedical and therapeutical fields. The results showed that sericin may be the most suitable silk materials to use as an alternative in tissue engineering compared with regenerated silk fibroin. It was found that sericin can absorb UV in the range of 223–300 nm, inhibit tyrosinase, resist to free radicals, and retain water capacity similar to hyaluronic acid. Importantly, cell experiment on human fibroblast showed that sericin (0.05 wt%) could stimulate cell proliferation and obviously up-regulate the expression of collagen type I, collagen type III, and hyaluronidase I compared with the control at seven days, which is the closest equivalent to regenerated silk fibroin. These results suggested that sericin might be a valuable ingredient for skin repair on tissue engineering.